PENGARUH PENAMBAHAN CMC (Carboxyl Methyl Cellulose) TERHADAP KARAKTERISTIK SIRUP SALAK BALI (Salacca zalacca var. Amboinensis) SELAMA PENYIMPANAN - Rahmaningtyas, Eka; Yusa, Ni Made; Puspawati, Ni Nyoman (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 2 (2016): Jurnal ITEPA, 2017)
The research was conducted to determine the effect of CMC ( Carboxyl Methyl Cellulose ) addition to characteristics the Bali snake fruit syrup during storage. The research was using randomized block design, with two factor, the first factor is CMC addition used was 0%, 0.25%, 0.50%, 0.75%, 1.00%, and 1.25%, the second factor is storage time used was 0 week, 2 week, 4 week, and 6 week. The parameters that was observed are viscosity, vitamin C, total sugar, total soluble solid, pH and sensory evaluation, such us taste, flavor, colour and overall acceptance. The results showed that interaction between CMC addition and storage time gave very significant effect on vitamin C. CMC addition gave very significant effect on viscosity, total sugar, and pH. Storage time gave very significant effect on vitamin C, pH, taste, flavor, colour, and overall acceptance. The best treatment Bali snake fruit syrup obtained in CMC addition 1.25% and storage time 4 week with characteristics objectif viscosity 2250.00 cP, vitamin C 12.56 mg/100g, total sugar 64.98 %, total soluble solid 38.00 o Brix, pH 3.70 and characteristics in sensory taste 5.13 (a little bit like), flavor 5.60 (like), colour 5.13 (a little bit like), overall acceptance 5.13 (a little bit like).
Keywords: syrup, Bali snake fruit, CMC addition and storage time